A Shallow Seabed Dynamic Gas Hydrate System off SW Taiwan: Results From 3‐D Seismic, Thermal, and Fluid Migration Analyses. Issue 11 (19th November 2020) - Kunath, Pascal; Chi, Wu‐Cheng; Berndt, Christian; Chen, Liwen; Liu, Char‐Shine; Kläschen, Dirk; Muff, Sina
Abstract: Large amounts of methane, a potent greenhouse gas, are stored in hydrates beneath the seafloor. Sea level changes can trigger massive methane release into the ocean. It is not clear, however, whether surficial seafloor processes can cause comparable discharge. Previously, fluid migration was difficult to study due to a lack of spatially dense seismic and thermal observations. Here we examine a gas hydrate site at Four‐Way‐Closure Ridge off SW Taiwan using a high‐resolution 3‐D seismic cube, together with bottom‐simulating reflections (BSRs) mapped in the cube, a thermal probe data set, and 3‐D thermal modeling results. We document, on a scale of tens of meters, the interaction between surficial sedimentary processes, fluid flow, and a dynamic gas hydrate system. Fluid migrates upward through dipping permeable strata in the limb, the slope basin, and along thrust faults and ridge‐top normal faults. The seismic data also reveal several double BSRs that underlie seabed sedimentary sliding and depositional features. Abrupt changes in subsurface pressure and temperature due to the rapid seabed sedimentary processes can cause a rapid shift of the base of the gas hydrate stability zone. This shift may be either downward or upward and would result in the accumulation or dissociation of hydrate in sediments sandwiched by the double BSRs, respectively. We propose that dynamic surficial processes on the seafloor together with shallow focused fluid flow affect hydrate distribution and saturation at depth and may even result in methane expulsion into the ocean if such localized features are common along convergent plate boundaries. Plain Language Summary: Gas hydrates are ice‐like compounds in marine sediments. Shallow surface dynamic processes may affect the hydrate saturation beneath the seabed. We combine 3‐D seismic and thermal probe data, with numerical geothermal modeling to investigate the geological processes controlling the distribution and formation of gas hydrates beneath thrust ridge anticlines. We also study fluid flow patterns under the seabed and found that localized fluid flow and rapid surficial erosional processes have significantly altered the temperature and pressure conditions of hydrate bearing sediment strata at depth, ultimately influencing gas hydrate formation and dissociation. We propose to conduct hydrate exploration close to thrust anticlines, where such active processes might enrich the saturation of gas hydrates or even influence fluid emission into the ocean if similar processes are widespread along continental margins. Key Points: Mass wasting and rapid sedimentation can generate double BSRs and enhance hydrate saturation Rapid seabed processes might trigger hydrate dissociation and active venting of methane and other fluids in shallow sedimentary section Focused fluid flow updip along the slope basin strata can locally enhance the hydrate saturation